Holocene and Last Interglacial climate of the Faroe Islands from sedimentary plant wax hydrogen and carbon isotopes. (1st November 2019) - Curtin, Lorelei; D'Andrea, William J.; Balascio, Nicholas; Pugsley, Genevieve; de Wet, Gregory; Bradley, Raymond
Abstract: The Last Interglacial period (LIG) is Earth's most recent globally warm period and is analogous in some ways to projected future global warming. However, questions remain regarding the state of the climate during the LIG in the North Atlantic, a region that is extremely sensitive to changes in oceanic and atmospheric circulation. Here, we present hydrogen and carbon isotope (δD and δ 13 C) records from a suite of plant wax biomarkers preserved in Holocene and LIG lacustrine sediments from the North Atlantic Faroe Islands and interpret them as qualitative proxies for temperature and hydroclimate variability. These data are used to directly compare LIG and Holocene climate using the same proxy approaches from the same terrestrial location. Measuring multiple isotopes on multiple types of waxes elucidates the sources of homologous plant waxes. We deduce that the δD values of long-chain n -alkanes (C27 –C33 ) and mid-chain n -alkanes (C23 –C25 ) in these sedimentary archives reflect leaf water and lake water δD values, respectively, while the δD values for both long-chain (C28 –C30 ) and mid-chain n-alkanoic acids (C24 –C26 ) primarily represent lake water δD values. Plant wax-inferred δD values of precipitation during the early Holocene (10, 100 to 8, 200  cal  yr BP) are ∼35‰ more positive than late Holocene values, and decline over the Holocene. δD-inferred hydrologic change and δ 13 C -inferred plant water use efficiency both indicate that the Faroe Islands became drier throughout the Holocene. Comparison with measurements from LIG plant waxes indicates that late LIG in the Faroe Islands was hydrologically similar to the early-to mid-Holocene (8, 200 to 4, 000  cal  yr BP), with enriched precipitation isotopes and reduced evapotranspiration indicating a warmer, wetter environment. Highlights: Holocene climate was characterized by a drying trend in the Faroe Islands. Leaf wax δD and water use efficiency from δ 13 C reveal the same drying trend. Decreased northward heat transport caused Holocene cooling and drying in the Faroes. North Atlantic climate in the late LIG was similar to the early to mid-Holocene.